Updates into the potential association between myeloproliferative neoplasms and inflammatory bowel disease - Adeniyi Abraham Adesola; Yongfeng Chen; Matei Alexandru Cozma; Mihnea-Alexandru Gama (Journal of the Pakistan Medical Association, 2024)
Inflammatory bowel disease (IBD) and myeloproliferative neoplasms (MPNs) are both chronic disorders in whose pathogenesis low-grade chronic inflammation plays a central contribution.1-3 IBD is characterised by chronic inflammation of the digestive tract, while MPNs are characterized by an overproduction of terminally differentiated myeloid cells.1,3 IBD may present itself mainly as ulcerative colitis (UC) or Crohn’s disease (CD) while the classical Philadelphia-negative MPNs comprise polycythemia vera (PV), essential thrombocythemia (ET) and primary/secondary myelofibrosis (MF).1,3 A recent cohort study found that subjects with MPNs have a 2.4-fold increased risk of developing IBD compared to individuals without MPNs. The risk of developing IBD was highest within the first year after the diagnosis of MPN and after five years of being diagnosed with an MPN. However, there was a lower risk of developing IBD between the first year and fifth year of being diagnosed with an MPN.4 These findings suggest that there may be a common underlying mechanism that drives the pathogenesis of both IBD and MPNs. Moreover, alterations of the gut microbiome have been described both in MPNs and IBD, possibly in direct relationship with the high concentrations of proinflammatory cytokines measured in these disorders.1,5 Continued...